2017
DOI: 10.1016/j.jacc.2017.07.793
|View full text |Cite
|
Sign up to set email alerts
|

Persistence With Dabigatran Therapy at 2 Years in Patients With Atrial Fibrillation

Abstract: Probability of treatment persistence with dabigatran after 2 years was approximately 70%. Nearly one-half of the patients who stopped dabigatran switched to another oral anticoagulant agent. Patients from North America, and those with paroxysmal, persistent, or symptomatic AF, may be at a higher risk for discontinuing dabigatran.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 22 publications
6
48
0
1
Order By: Relevance
“…These results are also comparable to the non‐persistence rate of rivaroxaban in patients with atrial fibrillation from the Dresden registry (19% at an average of 1.5 years of follow‐up), in which patients were frequently monitored by study design. A similar non‐persistent rate of 23% at 2 years of follow‐up for dabigatran was found in an observational study by Paquette et al, where AF patients on dabigatran were regularly monitored by study design (at 3, 6, 12 and 24 months). In short, all studies that found a low non‐persistence rate for oral anticoagulant use amongst patients with atrial fibrillation had presence of patient monitoring in common.…”
Section: Discussionsupporting
confidence: 81%
“…These results are also comparable to the non‐persistence rate of rivaroxaban in patients with atrial fibrillation from the Dresden registry (19% at an average of 1.5 years of follow‐up), in which patients were frequently monitored by study design. A similar non‐persistent rate of 23% at 2 years of follow‐up for dabigatran was found in an observational study by Paquette et al, where AF patients on dabigatran were regularly monitored by study design (at 3, 6, 12 and 24 months). In short, all studies that found a low non‐persistence rate for oral anticoagulant use amongst patients with atrial fibrillation had presence of patient monitoring in common.…”
Section: Discussionsupporting
confidence: 81%
“…All DOACs have proven efficacy compared with VKA, although at much lower time in therapeutic range (TTR) in trials than usual clinical practice, but ‘head-to-head’ DOAC trial comparisons are unlikely. However, several studies have shown suboptimal adherence and persistence for DOACs in different countries and settings, even compared with VKA, and effective interventions are lacking 12–14. Underlying causes include factors at social, economic, health system, clinician and patient levels.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports suggest a rapid decline in adherence to oral anticoagulation with vitamin K antagonists within the first years [ 11 , 12 ]. With the advent of the NOACs, higher adherence rates have been reported [ 13 , 14 , 15 ]. A retrospective analysis of primary care data in Germany reports about a persistence to apixaban after 1 year in 62.9% with apixaban and 57.5% with VKAs [ 16 ].…”
Section: Discussionmentioning
confidence: 99%